Effect of turmeric (Curcuma longa L.) extract on gastric histopathology of diclofenac sodium-induced rats - Melania Lie; Anita Lidesna Shinta Amat; Rahel Rara Woda; Kartini Lidia (Acta Biochimica Indonesiana, 2025)
Background: Prolonged use of diclofenac sodium can cause gastric mucosal damage through cyclooxygenase inhibition and oxidative stress. Turmeric (Curcuma longa L.) contains curcumin and other bioactive compounds with potential gastroprotective properties. Objective: To determine the dose-dependent gastroprotective effect of turmeric extract against diclofenac sodium-induced gastric mucosal injury in rats. Methods: This experimental study used 28 male Sprague-Dawley rats randomly allocated into four groups (n=7): normal control, negative control (diclofenac 10 mg/kgBW for 7 days), and two treatment groups receiving turmeric extract at 100 mg/kgBW (P1) or 200 mg/kgBW (P2) for 14 days following diclofenac induction. Gastric tissues were evaluated histopathologically using a qualitative description. Results: The negative control group showed severe erosion and inflammatory infiltration. Both treatment groups demonstrated gastroprotective effects with minimal epithelial damage and no inflammatory changes. The 200 mg/kgBW dose showed superior protection compared to 100 mg/kgBW. Conclusion: Turmeric extract provides dose-dependent gastroprotection against diclofenac-induced gastric injury, with 200 mg/kgBW demonstrating superior efficacy.